Perjanjian Kerahasiaan Bagi Karyawan Pengelola Data Pribadi Perusahaan - Dian Laksmi Dewi, Cokorde Istri; Rudin, Denny; Tungga, Benyamin (Kertha Patrika; Vol 46 No 2 (2024)DO - 10.24843/KP.2024.v46.i02.p02, 2024)
In a confidentiality agreement, the owner of personal data must maintain the security of the data by taking appropriate actions. This means that each step includes standards of reasonableness, feasibility, and propriety. The employee-employer relationship in possession of a trade secret is usually associated with maintaining the secret. The purpose of this research is to examine Company secrets rather than protecting personal data and discuss protecting Company secrets through confidentiality agreements. This normative legal study looks at statutory regulations and uses a problem approach by looking at literary sources and previous concepts of norms. The findings of this study show that employee personal data is a company secret, and there can be misuse of personal data by the company because leaking of it can be done by the company or not by the company. It is not impossible that there are parties who are not from companies who deliberately steal personal data to make a profit. Confidentiality agreements safeguard the interests of parties involved in business relationships or transactions within the company when the sharing of sensitive and personal information must be restricted from third-party access. This is a form of protection of company secrets which includes company data and employee personal data through a confidentiality agreement agreed by the superior and the employee. Confidential information is the essence of every confidentiality agreement.